Assessing national WaSH targets through a water governance lens: a case study of the Sanitation and Water for All partnership commitments - Leonie Schiedek (IWA Publishing, 2021)
Dysfunctional water, sanitation and hygiene (WaSH) systems are mainly determined by poor water governance, exacerbating inequalities and poverty. Multi-stakeholder partnerships provide an approach to more flexible and adaptive governance to explore these problems. In this article, national commitments made to improve WaSH, made through the Sanitation and Water for All (SWA) partnership's Mutual Accountability Mechanism, are examined through qualitative content analysis and guided by the SMART framework to assess the current target-setting. The analysis reveals that there are differences in the participation of the different constituencies regarding the number of stakeholders participating and their performance for measurable and time-bound commitments. This applies especially to research and learning and the private sector. Countries have prioritized commitments related to policy and strategy, efficiency and enabling conditions; further research should understand the linkages of the SWA commitments with other priority-setting processes at the national level. In sum, the commitments leave room for improvement to specify approaches to water governance in more detail and the chance to support the creation of sustainable and resilient systems with more diversified commitments from a wider range of partners. HIGHLIGHTS The importance of more equal participation of all constituencies needs to be underlined, since there are differences in general participation and performance for SMART goals.; Priorities in presenting certain governance components should be explored further to assess national goal-setting thoroughly.; Diversifying commitments could increase the potential of commitments to support creating sustainable and resilient systems.;